Analisis Karakteristik Bahan RAP Menggunakan Uji Adhesi Kimia, CBR, Dan UTM - Nugriawan, Dewangga Maytlas Dini, Ir. Agus Riyanto, M.t, Ir. Sri Sunarjono, M.T, PhD (2016)
RAP is the result of demolition of pavement, RAP be an alternative because material prices higher, this encouraging to utilize the waste that is damaged pavement for recycling. Related to this research because of the strength and durability of the pavement is often a major issue, because the carrying capacity and low deformation and poor adhesion. This study aimed to compare the chemical adhesion, the value of CBR, and deformation of UTM, the RAP and new aggregate material. This study uses laboratory tests. Physical examination was conducted on the test abrasion, density, gradation analysis, density analysis, asphalt examination was conducted on the density of asphalt, and asphalt penetration. After it was examined adhesion includes Immersion Chemical Coating Test Test and wet methods (W) and dry (D), as well as testing the value of CBR and deformation. The number of samples made as many as 66 samples. Overall value of chemical adhesion RAP, new aggregate and aggregate mixture has a good quality, while the value of CBR and UTM show RAP material is lower than the new aggregate. Chemical testing results obtained RAP Immersion test W=96.7%, D=97.3% , new aggregate W=98.7%, D=99% , mix aggregate W=98%, D=98.4%. Coating Test W RAP gained 96.9%, D=97.7%, new aggregate W=99.1%, D=99.7% of new aggregate, aggregate mixture obtained W=98.4%, and 98.7% for dry. RAP test results obtained maximum density of 1,59 g / cm3, the optimum water content of 5,27% to the value of CBR, CBR = 27,71%, UTM = 30,085%, The new aggregate density, maximum density of 1.81 g / cm3, the optimum water content of 5.72%, the value of CBR, CBR = 65,54%, UTM = 53,00%. The test results of deformation RAP using a CBR = 0,1 inch (600 lb), UTM = 0,27 inchi (1200lb), new aggregate CBR = 0,045 inch (1500lb) UTM = 0,12 inchi (940lb). The final conclusion is that the RAP and new aggregate material has good adhesion value, but the value of the carrying capacity and deformation of the material has low quality RAP.